Thyroid Dysfunctions Among Patients at Nepalgunj Medical College: A Hospital Based - BK, Shyam Kumar; Baral, Sushil; Bassi, S. D.; Joshi, S. D.; Gupta, Sandeep; Shah, Sujit Kr. (Journal of Nepalgunj Medical College, 2018)
Introduction: Thyroid disorders are prevalent and their manifestations are determined by the dietary iodine availability which is common in country. Thyroid dysfunction is common clinical finding among the people presenting to the hospital. Its prevalence increases with age. Screening of thyroid disease is advised in high risk population for the early diagnosis and treatment. Objective: Thyroid disfunction is most common clinical problem among male and female in Nepal. To find out thyroid disfunctions among patients at Nepalgunj Medical College. Methodology: This is a retrospective study carried out in the Department of Medicine, Nepalgunj Medical College, Nepal from January 2014 to June 2016 for the period of two years. A total of 200 patients who visited outpatient door with suspected thyroid disorders i.e. hypothyroidism, hyperthyroidism or to rule out thyroid disorders got their thyroid function test. Serum TSH and fT3 /fT4 estimations were carried out by Enzyme linked immune sorbent assay method. Result: Among 200 subjects, the prevalence of thyroid dysfunction was 20%. Females had more thyroid dysfunction than male. Hypothyroidism (15%) had higher prevalence compared to hyperthyroidism (5%). Higher prevalence of thyroid dysfunction was observed in patients between 14 - 45 years. Conclusion: This study revealed that hypothyroidism is predominant then hyperthyroidism. Females patients have more common thyroid dysfunction True population surveillance is difficult and hence, presently it was aimed to carry out hospital based study on the incidence of thyroid disorders. JNGMC, Vol. 14 No. 2 December 2016, Page: 66-69